CALCITONIN GENE RELATED PEPTIDE IS ELEVATED IN PATIENTS WITH ACUTE CORONARY SYNDROME. (29th November 2012) - Agnew, C P; Bell, D; Morrice, K W; Herity, N A; Harbinson, M T
Abstract : Introduction: Elevated blood levels of cardiac troponin (cTn) released during myocardial ischaemia/infarction define acute coronary syndrome (ACS). However, cTn is not detectable for 3–4 h after symptom onset. The peptide Calcitonin Gene Related Peptide (CGRP) is released from nerve endings during myocardial ischaemia and has cardioprotective effects. Aim: To determine if plasma CGRP is elevated in patients with ACS and could be an early marker of myocardial ischaemia. Methods: Blood was drawn from 80 patients with chest pain of possible cardiac origin at various time points from admission to discharge. Elevated cTnT (>0.03 ng/ml) defined patients with ACS. CGRP levels were measured by radioimmunoassay. Results: At 12 h after symptom onset, 46 results were available from 23 individuals without cTn rise (control) and 23 patients with ACS. CGRP was elevated in ACS patients (8.9±0.5 vs 6.8±0.5 pg/ml control; p=0.007). CGRP was elevated in both STEMI (9.2±0.9 pg/ml; n=15; p=0.02) and NSTEMI (8.7±0.7 pg/ml; n=34; p=0.03) patients. At first presentation, CGRP levels tended to be higher in ACS (8.4±0.6 pg/ml; n=20) than control (6.9±0.5 pg/ml; n=31; p=0.07) subjects. Eight patients with ACS presenting within 8 h of symptoms had normal initial cTn, but significantly elevated CGRP (9.3±0.8 pg/ml) compared with control (p=0.03). Conclusions: CGRP is elevated in patients with cTn positive ACS, both STEMI and NSTEMI. In patients presenting early (within 8 h), in whom cTn had not yet risen, CGRP was significantly elevated compared with control.